The Effectiveness of Concept Cartoons to Enhance Conceptual Understanding of Kinematic Concepts - Rohmi, Puspo (Jurnal Pembelajaran Fisika, 2024)
Understanding kinematic concepts is essential for students to develop a strong foundation in physics and to appreciate the basic principles of nature. This study aims to investigate the effectiveness of concept cartoons in enhancing the conceptual understanding of kinematic concepts among students. This research is an experimental study using a pretest-posttest control group design with two class VII of junior high schools as samples. In both classes, learning was carried out on the topic of kinematics, where the experimental group was given treatment in the form of implementing concept cartoons embedded in worksheets and the control group only used structured worksheets with the same learning model. Based on the results of the pretest and posttest using a reasoned multiple choice objective test instrument, a normalized average gain value was obtained which shows the effectiveness of increasing students' conceptual understanding in both classes after being given treatment, with the experimental group achieving a 0.45 (medium category) normalized gain, higher than the 0.13 (low category) gain in the control group. The statistical test results of the t-test showed that there was a statistically significant difference in enhancement of students' conceptual understanding about kinematic concepts between the experimental group and control group. In addition, during the learning process, students in the experimental group appeared to be more active in discussions. By using concept cartoons, teachers can identify misconceptions experienced by studentsKeywords: Concept cartoons, conceptual understanding, kinematic concepts, misconception, worksheetsDOI: http://dx.doi.org/10.23960/jpf.v12.n1.202405